2021
DOI: 10.1021/acs.jafc.0c06685
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis Reveals the Importance of Exudates on Sclerotial Development in Sclerotinia sclerotiorum

Abstract: Sclerotinia sclerotiorum is a ubiquitous necrotrophic pathogenic fungus causing significant losses in a broad range of plant species. Sclerotia formed by S. sclerotiorum play important roles in both the fungal life cycle and the disease development cycle. Sclerotial exudation during sclerotial development is a characteristic feature of this fungus. In this study, a proteome-level investigation of proteins present in sclerotial exudates was conducted by high-throughput LC–MS/MS analysis. A total of 258 proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…This fungal pathogen poses a threat to dicotyledonous crops such as sunflower, soybean, peanut, oilseed rape, lentils and various vegetables, but also monocotyledonous species such as onion, tulip, and garlic [4]. This fungus can produce sclerotia, which serve as long-term survival structures under adverse environments and play critical roles in disease progression [5,6]. Another necrotrophic pathogen, Botrytis cinerea, causes grey mold disease in a variety of fruit and vegetables [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This fungal pathogen poses a threat to dicotyledonous crops such as sunflower, soybean, peanut, oilseed rape, lentils and various vegetables, but also monocotyledonous species such as onion, tulip, and garlic [4]. This fungus can produce sclerotia, which serve as long-term survival structures under adverse environments and play critical roles in disease progression [5,6]. Another necrotrophic pathogen, Botrytis cinerea, causes grey mold disease in a variety of fruit and vegetables [7].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted that S. sclerotiorum and B. cinerea are closely related based on their genome sequences [7,8]. Plant-pathogenic fungi can facilitate an infection in their hosts by the secretion of a wide array of cell-wall-degrading enzymes (CWDEs), including cellulases (glucanase), pectinases (polygalacturonase), glycosidases, xylanases and cutinases [5,6]. In addition, S. sclerotiorum and B. cinerea are known to produce oxalic acid to promote infection [7].…”
Section: Introductionmentioning
confidence: 99%
“…Among the studies focused on exudate investigations, the following media were utilized: potato dextrose agar [ 17 , 18 ], malt extract agar [ 19 , 20 ], and potato sucrose agar [ 21 ]. These were rarely specialized media, and involved synthetic, natural, and combined [ 15 , 22 , 23 , 24 ]. Hutwimmer et al [ 15 ] indicated how big impact on a fungal guttation has the composition of sugars in growth medium.…”
Section: Conditions and Factors Promoting Guttationmentioning
confidence: 99%
“…Recent reports showed even larger numbers of secreted proteins. In exudate droplets of S. sclerotiorum , researchers identified a total of 258 proteins [ 22 ], in Cercospora armoraciae —576 proteins [ 25 ], while in exudates of Ustilaginoidea virens— 650 various proteins were detected [ 21 ]. Proteomic analysis of S. sclerotiorum exudates overlapped to some degree with earlier observations—four proteins were recognized as being related to plant cell wall degradation, contributing to host tissue necrosis [ 22 ].…”
Section: Proteins Excreted By Guttationmentioning
confidence: 99%
See 1 more Smart Citation